A Critical Evaluation of Islamic Economic Growth in Developing Countries - Ismaulina Chairawan; Iskandar Iskandar; Azharsyah Ibrahim (Universitas Islam Negeri Ar-Raniry, 2026)
Persistent socio-economic disparities and growing concerns over ethical economic governance have renewed interest in Islamic economics as an alternative development paradigm in the Global South. While conceptually compelling, its real-world application continues to face structural, institutional, and policy-related constraints that limit its transformative capacity. This study critically evaluates the development trajectory of Islamic economics in selected developing countries, focusing on the alignment of spiritual values with public policy and economic systems. A qualitative, reflective-descriptive design is employed using document analysis grounded in institutional theory, Islamic moral economy, and adaptive policy frameworks. The data consist of scholarly publications, official reports, and strategic policy documents published between 2015 and 2025, with particular attention to OIC member countries, including Indonesia, Malaysia, Saudi Arabia, and Pakistan. Thematic analysis reveals that strong institutions, flexible regulatory environments, and digital readiness are central to effective Islamic economic transformation. However, uneven regional development, non-contextualized policy designs, limited stakeholder engagement, and weak integration of Islamic economic education remain persistent challenges. The findings further indicate that policy interventions often remain symbolic due to the absence of dialogical and participatory governance mechanisms. Theoretically, this research advances understanding of how maqasid al-shariah can be translated into sustainable development practices. Practically, it offers direction for cross-sectoral collaboration, educational reform, and inclusive digital infrastructure. Overall, the study highlights the importance of a glocal approach that balances local socio-cultural realities with global development aspirations. ABSTRAK - Evaluasi Kritis Pertumbuhan Ekonomi Syariah di Negara-negara Berkembang. Ketimpangan sosial-ekonomi yang terus berlanjut serta meningkatnya tuntutan terhadap tata kelola ekonomi yang beretika telah mendorong ekonomi Islam kembali dipandang sebagai paradigma pembangunan alternatif di negara-negara berkembang. Meskipun kuat secara konseptual, implementasi ekonomi Islam dalam praktik masih dihadapkan pada berbagai keterbatasan struktural, kelembagaan, dan kebijakan yang menghambat daya transformasinya. Penelitian ini mengkaji secara kritis dinamika perkembangan ekonomi Islam di sejumlah negara berkembang dengan menyoroti keterpaduan nilai-nilai spiritual, kebijakan publik, dan sistem ekonomi. Penelitian menggunakan pendekatan kualitatif dengan desain reflektif-deskriptif melalui analisis dokumen, yang berpijak pada teori kelembagaan, ekonomi moral Islam, dan kerangka kebijakan adaptif. Sumber data meliputi artikel ilmiah, laporan resmi, dan dokumen kebijakan strategis yang diterbitkan pada periode 2015–2025, dengan fokus pada negara anggota OKI seperti Indonesia, Malaysia, Arab Saudi, dan Pakistan. Hasil analisis tematik menunjukkan bahwa kekuatan institusi, fleksibilitas regulasi, dan kesiapan digital merupakan faktor kunci dalam mendorong transformasi ekonomi Islam. Namun, kesenjangan regional, kebijakan yang kurang kontekstual, rendahnya partisipasi pemangku kepentingan, serta lemahnya integrasi pendidikan ekonomi Islam masih menjadi tantangan utama. Secara teoretis, penelitian ini memperkaya pemahaman mengenai penerapan maqasid al-shariah dalam kerangka pembangunan berkelanjutan. Secara praktis, temuan penelitian memberikan arahan kebijakan untuk memperkuat kolaborasi lintas sektor, reformasi pendidikan, dan pembangunan infrastruktur digital yang inklusif melalui pendekatan glokal.